THE ROLE OF FOREIGN INVESTMENT IN THE DEVELOPMENT OF THE IRAQI TOURISM SECTOR (Neo Scientific Peer Reviewed Journal, 2023)
Foreign investment in our contemporary world is considered one of the most prominent ways to advance the reality of nations and peoples, especially developing peoples, in order to increase job opportunities, reduce unemployment, eradicate poverty, and improve living conditions in all economic, social, cultural and environmental fields, where investment is one of the most important means of financing for these Nations and peoples and help them in economic development.This prompted many countries, including Iraq, to issue laws and decisions that encourage foreign investments to enter these countries. Since the eighties of the last century, Iraq has sought to issue laws and take measures to attract domestic and foreign capital. However, the political and military circumstances led to a major stumbling block in this vital field. And since tourism occupies a prominent place in many national strategies and plans set by countries, as an economic activity with positive economic, social and cultural effects, so foreign investment in this sector can achieve the desired development.And since it has a leading tourist center in the Middle East region due to its historical, cultural and religious status, and its distinguished geographical location, its tourism sector, like other economic sectors, faces many challenges that stand in the way of its development.